Experimental Study of the Plasma Polymerization of Ethyl Lactate. Issue 11 (17th September 2013) - Ligot, Sylvie; Renaux, Fabian; Denis, Laurent; Cossement, Damien; Nuns, Nicolas; Dubois, Philippe; Snyders, Rony
Abstract In this work, we report on the synthesis of ethyl lactate‐based plasma polymer film (ELPPF) by plasma enhanced chemical vapour deposition (PECVD). Using a design of experiments, it appears that, among other, the injected power (PRF) is the key parameter affecting the ELPPF features. Indeed, we observe a strong decrease of the COO‐C/H functionalities (from 12 to 2 at.%) within a limited PRF domain. A more precise analysis of the film chemistry by combining XPS and chemical derivatization reveals that up to 95% of these carboxyl‐based functions are esters. On the other hand, we show that the cross‐linking degree of the ELPPF can be increased by a factor of two as a function of PRF. This work paves the way for the tailoring of the barrier properties of ELPPF by controlling the ester content and the cross‐linking degree of the PPF.<inline-graphic xlink:href="ark:/27927/pgg3wjnb96t" content-type="ppap201300025-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />